2018
DOI: 10.1016/j.protis.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Chytrid-like Parasites of Algae Amoeboradix gromovi gen. et sp. nov. and Sanchytrium tribonematis Belong to a New Fungal Lineage

Abstract: Fungi encompass, in addition to classically well-studied lineages, an ever-expanding diversity of poorly known lineages including zoosporic chytrid-like parasites. Here, we formally describe Amoeboradix gromovi gen. et sp. nov. comprising a set of closely related strains of chytrid-like parasites of the yellow-green alga Tribonema gayanum unusually endowed with amoeboid zoospores. Morphological and ultrastructural features of A. gromovi observed by light and transmission electron microscopy recall previous des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…Recently, we obtained 18S and 28S rRNA gene data for Amoeboradix gromovi, a chytrid-like fungus having peculiar traits and resembling the classical Rhizophydium anatropum. Surprisingly, phylogenetic analyses of these two markers showed that Amoeboradix formed a tight cluster with another chytrid-like organism, Sanchytrium tribonematis, branching in a basal position to the Glomeromycota and Dikarya cluster, albeit with low support (Karpov et al 2018). The Amoeboradix-Sanchytrium clade is very divergent and represents a new fungal lineage.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, we obtained 18S and 28S rRNA gene data for Amoeboradix gromovi, a chytrid-like fungus having peculiar traits and resembling the classical Rhizophydium anatropum. Surprisingly, phylogenetic analyses of these two markers showed that Amoeboradix formed a tight cluster with another chytrid-like organism, Sanchytrium tribonematis, branching in a basal position to the Glomeromycota and Dikarya cluster, albeit with low support (Karpov et al 2018). The Amoeboradix-Sanchytrium clade is very divergent and represents a new fungal lineage.…”
mentioning
confidence: 98%
“…Surprisingly, phylogenetic analyses of these two markers showed that Amoeboradix formed a tight cluster with another chytrid‐like organism, Sanchytrium tribonematis, branching in a basal position to the Glomeromycota and Dikarya cluster, albeit with low support (Karpov et al. ). The Amoeboradix‐Sanchytrium clade is very divergent and represents a new fungal lineage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with an ancient origin of all three phenotypes, amoeboid, flagellate and amoeboflagellate cells are all broadly distributed in opisthokonts (animals, fungi, and their relatives). Interestingly, amoeboflagellate phenotypes have recently been described in several species occupying key phylogenetic positions, including in the sister-group of choanozoans (the filastereans) 37,38 , in early-branching fungi 39,68,69 , in the two closest known relatives of opisthokonts (apusomonads 70 and breviates 71 ), and in early-branching amoebozoans 72 . This is consistent with an ancient origin and broad conservation of the amoeboflagellate phenotype in opisthokonts 73 .…”
mentioning
confidence: 99%